STRATEGI KOMUNIKASI KRISIS PEMERINTAH KABUPATEN LAMONGAN DALAM MENANGGAPI ISU KERUSAKAN JALAN - Felia Dwi Anjarsari, Yan; Suratnoadji, Catur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Road repair concerns in Lamongan Regency have sparked significant public dissent and diminished faith in the local administration, especially through the swift sharing of grievances on social platforms. This scenario has shifted from an issue of infrastructure to a challenge in communication that necessitates a strong crisis communication plan. This research is designed to examine the crisis communication tactics used by the Lamongan Regency Government to tackle the road repair dilemma, utilizing Benoit's Apologia Theory. The investigation followed a qualitative descriptive strategy within a constructivist framework. Information was gathered via detailed interviews, monitoring government interactions on social media, and reviewing documents, which were then analyzed using interactive data analysis methods that included data reduction, presentation, and drawing conclusions. The results indicate that the Lamongan Regency Government employed all six strategies of Apologia: denial, bolstering, differentiation, transcendence, corrective action, and mortification. Notably, corrective action and differentiation proved to be the most prevalent strategies, focusing on factual clarity, clarification of government roles, openness about planning and budgeting, and ongoing updates on infrastructure development. In contrast, mortification was the least utilized strategy, with formal public apologies seldom issued through official communication channels. The study concludes that the government's approach to crisis communication primarily aimed to rebuild public confidence by emphasizing transparency, clarification, and concrete corrective measures instead of relying on emotional responses. These results underscore the vital role of strategic, clear, and consistent communication in enhancing the reputation and trustworthiness of local governments amid public crises.